Solution-processible 1, 3, 4-oxadiazole/spiro[fluorene-9, 9′- xanthene] hybrid as efficient host for green thermally activated delayed fluorescence devices. (July 2019) - Zhao, Xiang-Hua; Wang, Jing-Yuan; Wu, Jia-Xing; Li, Yue; Zou, Guo-Dong; Xie, Guohua; Lin, Zong-Qiong; Xie, Ling-Hai; Zhang, Xin-Wen; Zhao, Jian-Feng
Abstract: A novel bulky 1, 3, 4-oxadiazole-based spirocyclic compound 2, 5- bis (2-spiro[fluorene-9, 9′-xanthene]-7-yl)phenyl)-1, 3, 4-oxadiazole (D- [2-SFXP]- o -OXD) has been synthesized successfully by incorporating spiro[fluorene-9, 9′-xanthene] (SFX) into 2, 5-biphenyl-1, 3, 4-oxadiazole reaction via Suzuki cross-coupling with Pd(PPh3 )4 as catalyst. The electrochemical properties of the compound were researched via cyclic voltammetry (CV) and obtained the HOMO, LUMO, and energy gap (Eg, 3.57 eV). The green TADF OLEDs hosted D[2-SFXP]- o -OXD and D[2-SFXP]- o -OXD: m CP by solution-processing techniques with maximum current efficiency (CE) and EQE (external quantum efficiency) of 15.2 cd A −1 /4.8% and 25.9 cd A −1 /8.5% as the doping concentration increasing from 5% to 10%, respectively. The electroluminescent (EL) spectra are independent of the concentration changes, which exhibits the three dimensional bulky D[2-SFXP]- o -OXD with large steric hindrance could successfully suppress the concentration quenching and excimer emission. Graphical abstract: This is the first 1, 3, 4-oxadiazole-based spiro-annulation compound as host for TADF OLEDs.Image 1 Highlights: This is the first 1, 3, 4-oxadiazole-based spiro-annulation compound as host for TADF OLEDs. A navel 1, 3, 4-oxadiazole-based spiro-annulation compound was designed and synthesized. The 3D bulky D[2-SFXP]- o -OXD could successfully suppress the concentration quenching and excimer emission demonstrated by the electroluminescent spectra under different doping concentration.